Development of the Domino Pericyclic Oxy-Cope/Ene /Claisen /Diels-Alder Reaction and the Synthesis of Complex Bicyclo[3.3.1]alkenones - Sow, Boubacar (Université d'Ottawa / University of Ottawa, 2014)
This thesis is a dissertation to support the development of new domino pericyclic oxy-Cope/ene/Claisen/Diels-Alder reaction, diversity oriented synthesis of PPAPs scaffold via sequential one pot cascade reaction and ethyl aluminum sesquichloride catalyzed highly hindered Diels-Alder reaction. The first part concentrates on the domino pericyclic oxy-Cope/ene/Claisen/Diels-Alder reaction. As a result of this study, we have developed a general methodology for rapidly constructing complex diterpenes and discovered a thermal oxy-Cope/ene/Claisen/Claisen rearrangement, applied to the synthesis of trans decalin benzofurans. The second part involved the development of an efficient synthetic approach towards bicyclo[3.3.1]nonenone core found in many natural products, via a sequential Diels-Alder/gold(I)-catalyzed 6-endo-dig cyclization and its application to the synthesis of a diversified library of PPAPs. Finally, we have developed an efficient synthetic methodology for the formation of cyclohexene rings bearing quaternary carbon centers via an ethyl aluminum sesquichloride mediated highly hindered Diels-Alder reaction. This method solved an important problem encountered in the synthesis of many natural products including PPAPs. This methodology opened new opportunities in the total synthesis of PPAPs.
Keywords: PPAP; Domino; Organic synthesis; Gold catalysis; Sesquichloride